Efektivitas Penegakan Hukum Tindak Pidana Terorisme oleh Detasemen Khusus 88 Anti Teror (Densus 88 At) Polri dalam Perspektif Undang-Undang No. 5 Tahun 2018 Tentang Terorisme - Akbar Ragiel Ar’rasyiid; Padimun Lumban Tobing (PT Elaborium Elevasi Indonesia, 2026)
This study assesses the effectiveness of law enforcement against terrorism crimes committed by Detasemen Khusus 88 Anti Teror (Densus 88 AT) Polri after the enactment of Law Number 5 of 2018 About Terrorism. Using a normative juridical method with a legislative and conceptual approach as well as supported by empirical data from relevant institutional reports, this study examines the aspects of prevention, investigation, and enforcement. The results of the analysis show that Law No. 5 of 2018 About Terrorism strengthens the legal basis for preventive and repressive actions. Including aspects of wiretapping, early arrest, detention, and rapid search, these aspects contribute to an increase in the ability to thwart attack plans and uncover terrorist networks. However, the effectiveness of law enforcement is also influenced by the quality of intelligence, the quality of technology, the competence of human resources, and the smooth coordination between institutions. In addition, opaque enforcement practices raise concerns about human rights and public perceptions of these powers. Recommendations from this study include the formulation of technical operational guidelines, strengthening internal and external oversight mechanisms, improving the quality of technology, and strengthening deradicalization programs to ensure that these powers are exercised effectively.